RELATIONSHIP OF SEDENTARY LIFESTYLE AND INTENSITY OF DYSMENORRHEA IN MIDWIFE STUDENTS FACULTY OF MEDICINE SEBELAS MARET UNIVERSITY - Rafiqa Aprilya, Anes; Kusmawati, Iffah Indri; Putri, Noviyati Rahardjo; Nurhidayati, Siti; Nurinasari, Hafi (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2024)
Background: Dysmenorrhea is a menstrual syndrome disorder that generally occurs in women of reproductive age before or during menstruation in a form of pain and discomfort around the pelvis, lower abdomen, and back. One of dysmenorrhea factors is the lack of daily physical activity (sedentary lifestyle). Sedentary lifestyle can cause ischemia that blocks the blood flow to the reproductive organs and the production of endorphins which help in reducing pain during menstruation.Objectives: To find out the correlation between sedentary lifestyle and the dysmenorrhea intensity among midwifery students, Faculty of Medicine, Sebelas Maret University.Method: This study used a quantitative method by applying a cross-sectional approach. The population of this study were 107 midwifery students. The sampling used a purposive sampling technique with the result of 85 respondents. The univariate data analysis used frequency distribution, while the bivariate analysis used Spearman Rank test with ?-value < 0.05.Result: The result showed that the majority of midwifery students of Medical Faculty, Sebelas Maret University, with low sedentary lifestyle were 52 respondents (61.2%) and the majority of the students with low dysmenorrhea intensity were 53 respondents (63%). There was a significant and strong connection between sedentary lifestyle and dysmenorrhea intensity among midwifery students (ρ-value=0.000) and (r=0.930).Conclusion: The positive value of the correlation showed a unidirectional relation between two variables where the higher sedentary lifestyle was, the higher dysmenorrhea intensity that would be experienced. There is a correlation between sedentary lifestyle and dysmenorrhea intensity.